Addressing unwarranted clinical variation: A rapid review of current evidence. Issue 1 (15th May 2018) - Harrison, Reema; Manias, Elizabeth; Mears, Stephen; Heslop, David; Hinchcliff, Reece; Hay, Liz
Abstract: Introduction: Unwarranted clinical variation (UCV) can be described as variation that can only be explained by differences in health system performance. There is a lack of clarity regarding how to define and identify UCV and, once identified, to determine whether it is sufficiently problematic to warrant action. As such, the implementation of systemic approaches to reducing UCV is challenging. A review of approaches to understand, identify, and address UCV was undertaken to determine how conceptual and theoretical frameworks currently attempt to define UCV, the approaches used to identify UCV, and the evidence of their effectiveness. Design: Rapid evidence assessment (REA) methodology was used. Data sources: A range of text words, synonyms, and subject headings were developed for the major concepts of unwarranted clinical variation, standards (and deviation from these standards), and health care environment. Two electronic databases (Medline and Pubmed) were searched from January 2006 to April 2017, in addition to hand searching of relevant journals, reference lists, and grey literature. Data synthesis: Results were merged using reference‐management software (Endnote) and duplicates removed. Inclusion criteria were independently applied to potentially relevant articles by 3 reviewers. Findings were presented in a narrative synthesis to highlight key concepts addressed in the published literature. Results: A total of 48 relevant publications were included in the review; 21 articles were identified as eligible from the database search, 4 from hand searching published work and 23 from the grey literature. The search process highlighted the voluminous literature reporting clinical variation internationally; yet, there is a dearth of evidence regarding systematic approaches to identifying or addressing UCV. Conclusion: Wennberg's classification framework is commonly cited in relation to classifying variation, but no single approach is agreed upon to systematically explore and address UCV. The instances of UCV that warrant investigation and action are largely determined at a systems level currently, and stakeholder engagement in this process is limited. Lack of consensus on an evidence‐based definition for UCV remains a substantial barrier to progress in this field.